Socio-economic correlates and management implications of livestock depredation by large carnivores in the Tarangire ecosystem, northern Tanzania. Issue 1 (1st January 2017) - Mkonyi, Felix J.; Estes, Anna B.; Msuha, Maurus J.; Lichtenfeld, Laly L.; Durant, Sarah M.
ABSTRACT: Livestock depredation by large carnivores is the key source of human–carnivore conflict worldwide and entails financial losses to livestock keepers. We examined the extent and patterns of livestock depredation, the financial impacts of livestock losses and determinants of livestock depredation by large carnivores in the Tarangire ecosystem of northern Tanzania. Of 300 households surveyed, 74.7% reported losses of 1906 livestock to wild predators over 1.5 years, which represents an annual loss rate of 1.4% of their total herd. Spotted hyena ( Crocuta crocuta ) accounted for 70% of the total livestock loss, followed by leopard ( Panthera pardus ) (12%), African wild dog ( Lycaon pictus ) (8%), lion ( Panthera leo ) (7%) and cheetah ( Acinonyx jubatus ) (3%). This loss equated to a total financial loss of US141, 847 amounting to approximately US633/household/year. Depredation frequency by all carnivore species increased significantly with increasing number of livestock owned, respondent's residency time, distance from the park boundary and declined significantly with increasing education, number of herders and improved fortified boma for cattle. Livestock depredation peaked during the wet season linked to seasonal migration of wild prey. Our study suggests that improving formal and conservation awareness education, boma fortification as well as improving herding practices could help mitigate the human–carnivore conflict.EDITED BY Carsten Smith-Hall